SISTEM INFORMASI BERBASIS WEBGIS JARINGAN IRIGASI PERSAWAHAN POPONTOLEN KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - Benny .; Robert Molenaar; Sandra E. Pakasi (Universitas Sam Ratulangi, 2019)
ABSTRACT This study aims to create an application of geospatial information on irrigation networks in Popontolen Village that supports the online monitoring and maintenance of irrigation networks based on WebGIS. This information system can be built using computers with low specifications and is supported by easy and free software (open source). This WebGIS design utilizes the framework of QGIS and the Bootstrap framework for the overall appearance of WebGIS, both of which have a programming language for displaying WebGIS. By utilizing free hosting services that are available, this WebGIS prototype can be accessed by internet users by typing the URL in the address bar https://sijaripopontolen.000webhostapp.com/index.html. And can be displayed on various devices both desktop and mobile-based. Keywords : Irrigation Networks,